2016
DOI: 10.3389/fmicb.2016.01095
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Arbuscular Mycorrhizal Fungi in the Restoration of Degraded Lands

Abstract: Experiences worldwide reveal that degraded lands restoration projects achieve little success or fail. Hence, understanding the underlying causes and accordingly, devising appropriate restoration mechanisms is crucial. In doing so, the ever-increasing aspiration and global commitments in degraded lands restoration could be realized. Here we explain that arbuscular mycorrhizal fungi (AMF) biotechnology is a potential mechanism to significantly improve the restoration success of degraded lands. There are abundant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
149
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 215 publications
(153 citation statements)
references
References 147 publications
(272 reference statements)
1
149
0
3
Order By: Relevance
“…Degraded lands harbor low levels of AMF abundance and diversity [19]. Many studies found that disturbance of semi-arid ecosystems decreased mycorrhizal spore density and root colonization [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Degraded lands harbor low levels of AMF abundance and diversity [19]. Many studies found that disturbance of semi-arid ecosystems decreased mycorrhizal spore density and root colonization [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The function of AMF in exclusion process and knowledge of AMF diversity in a specific area is essencial to utilize AMF in any application (Wang and Zao 2008). The very few conditions where infective AMF are low in density and diversity is when the soil erodes, is disturbed, and is devoid of vegetation cover (Asmelash et al 2016). The presence of enough AMF propagules in a restored site facilitates the establishment of plant communities through increased availability of nutrients and moisture to plant roots (Asmelash et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The very few conditions where infective AMF are low in density and diversity is when the soil erodes, is disturbed, and is devoid of vegetation cover (Asmelash et al 2016). The presence of enough AMF propagules in a restored site facilitates the establishment of plant communities through increased availability of nutrients and moisture to plant roots (Asmelash et al 2016). Though exclosures positively contributed to land rehabilitation, there are limited studies on the role of exclosures to restore arbuscular mycorrhizal fungi.…”
Section: Introductionmentioning
confidence: 99%
“…a narrow focus on plant community composition may not provide accurate projections of future progress (Herrick et al ). Nonetheless, understanding is growing for biotic indicator groups such as lichens (Giordani et al ), mycorrhizal fungi (Ingleby et al ; Vogelsang et al ; Asmelash et al ), bryophytes (Karger et al ), herbs (McLachlan & Bazely ), overall soil quality (Ritz et al ), soil invertebrates (Lavelle et al ) including earthworms (Guéi & Tondoh ), arthropods (Longcore ; Pearce & Venier ; Schmidt et al ) including ants, (Folgarait ; Andersen & Majer ), saproxylic beetles (Lachat et al ; Audino et al ), and single‐species indicators (Siddig et al ). A recent review found 54 empirical studies that used invertebrates as indicators of restoration success, particularly at mine sites.…”
Section: Potential Indicatorsmentioning
confidence: 99%